Expressão gênica e hemodinâmica do trato reprodutivo de vacas nelore (Bos indicus) tratadas com diferentes indutores da ovulação e eCG em protocolos de IATF - FRANÇA, Itamara Gomes de (2022)
Forty Nelore cows were submitted to timed artificial insemination (TAI) protocol and randomly assigned to groups according to estradiol (E2) ester (cypionate or benzoate, i.e. EC or EB) and equine chorionic gonadotrophin treatment (eCG or No-eCG) in a factorial 2x2 design. On a random day of the estrous cycle (Day 0), cows received a P4 intravaginal device plus 2 mg im injection of EB. At the time of P4 device removal (Day 8), cows were treated with 0.150 mg im of D-cloprostenol (PGF) and randomly divided to receive or not 400 UI im of eCG, as well as randomly assigned to receive 1 mg of EC immediately (D8), or 1 mg of BE, 24 h after it (D9) as ovulatory stimuli. Therefore, the groups formed were EC, EC+eCG, EB and EB+eCG. Were evaluated the effects of treatments on VEGF, OXTR, and PGR gene expression, E2/P4 concentrations, and Doppler-flowmetry of the reproductive tract. Ovulation rate was higher in animals subjected to the EC + eCG treatment (p < 0.05). Follicular vascularization was not influenced by the ovulation inducer (p > 0.05), although it was influenced by the eCG treatment (p < 0.05). EB enabled higher vascularized area rate in CL (P = 0.0192). VEGF and PGR genes were more expressed in animals treated with EB and eCG. On the other hand, OXTR expression was less evident in eCG-treated cows. EC has led to higher E2:P4 ratio in follicular fluid. This outcome indicated higher follicular estrogenic activity at D10, which justified the higher ovulation rate, when EC was associated with eCG (p < 0.05). Finally, the results of the present study corroborate the hypothesis that the different E2 esters and eCG differentially regulate vascularization, steroidogenesis, and utero-ovarian gene expression in Bos indicus cows submitted to TAI protocols.